Models, Algorithms, and Technologies for Network Analysis Proceedings of the First International Conference on Network Analysis - Goldengorin, Boris; Kalyagin, Valery A.; Pardalos, Panos M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This volume contains a selection of contributions from the "First International Conference in Network Analysis," held at the University of Florida, Gainesville, on December 14-16, 2011. The remarkable diversity of fields that take advantage of Network Analysis makes the endeavor of gathering up-to-date material in a single compilation a useful, yet very difficult, task. The purpose of this volume is to overcome this difficulty by collecting the major results found by the participants and combining them in one easily accessible compilation. Network analysis has become a major research topic over the last several years. The broad range of applications that can be described and analyzed by means of a network is bringing together researchers, practitioners and other scientific communities from numerous fields such as Operations Research, Computer Science, Transportation, Energy, Social Sciences, and more. The contributions not only come from different fields, but also cover a broad range of topics relevant to the theory and practice of network analysis, including the reliability of complex networks, software, theory, methodology, and applications.
Keywords: Mathematics; Combinatorics; Mathematical optimization; Mathematics; Optimization; Combinatorics; Operations Research, Management Science